2020
DOI: 10.21470/1678-9741-2019-0408
|View full text |Cite
|
Sign up to set email alerts
|

Valve Heart Surgery in Brazil – The BYPASS Registry Analysis

Abstract: Objective: To analyze the profile and outcomes of patients who underwent valve heart surgery in Brazil, using information retrieved from the Brazilian Registry of Cardiovascular Surgeries in Adults (BYPASS Registry) database.Methods: This is a multicenter cohort study, evaluating 920 patients submitted to heart valve surgery. Demographics and postoperative clinical outcomes were assessed and compared to estimate mortality risk using the European System for Cardiac Operative Risk Evaluation (EuroSCORE).Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This was expected, since in underdeveloped and developing countries like Brazil, this disease remains endemic, and is the main etiology of valve dysfunction. [7][8][9] In addition, it is known that its prevalence is higher in the female population, 7 which has been confirmed by most studies on valve disease. 8,[11][12][13][14][15][16] As observed in the present study, mean age of patients undergoing valve replacement due to rheumatic etiology is relatively low, in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This was expected, since in underdeveloped and developing countries like Brazil, this disease remains endemic, and is the main etiology of valve dysfunction. [7][8][9] In addition, it is known that its prevalence is higher in the female population, 7 which has been confirmed by most studies on valve disease. 8,[11][12][13][14][15][16] As observed in the present study, mean age of patients undergoing valve replacement due to rheumatic etiology is relatively low, in accordance with previous studies.…”
Section: Discussionmentioning
confidence: 75%
“…[7][8][9] In addition, it is known that its prevalence is higher in the female population, 7 which has been confirmed by most studies on valve disease. 8,[11][12][13][14][15][16] As observed in the present study, mean age of patients undergoing valve replacement due to rheumatic etiology is relatively low, in accordance with previous studies. 12,15,17 On the other hand, participants of studies carried out in high-income countries are older, due to the predominance of degenerative and ischemic etiology of valve disease.…”
Section: Discussionmentioning
confidence: 75%
“…The Brazilian registrY of adult Patients undergoing cArdiovaScular Surgery (or BYPASS), a recent Brazilian registry, organized by the Brazilian Society of Cardiovascular Surgery analyzing data on valve surgeries from 920 patients (80% from the public and 20% from the private healthcare system of 17 different institutions in the country), found a mortality in aortic valve replacement isolated of 5.1% and 14.7% in aortic valve replacement associated with CABG. In this analysis, when only interventions in aortic degenerative disease were evaluated, the mortality was 7.8% [ 20 ] . It is worth emphasizing that this analysis included data from more than twenty years of interventions, representing nearly three decades and covering different stages of cardiac surgery within PUCRS hospital.…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, it was observed that in aortic valve replacement surgery combined with CABG compared to isolated valve replacement, there is an increased risk of death. Based on the abovementioned national studies, an increase of at least two to three times in the risk of death for combined surgery can be seen [ 17 , 18 , 20 ] . Regarding to STS Score and the United Kingdom cohorts, it was observed a less than twofold increase in associated surgery mortality compared to isolated aortic valve, and in New York State cohort, it was twice as high [ 5 , 6 , 14 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Following the establishment of the Society of Thoracic Surgeons (STS) Adult Cardiac Surgery Database in 1989, many other national and continental databases were instituted to gather information on current trends and to improve the quality assessment and advance of cardiovascular surgery in their respective areas [ 2 ] . An important headway was provided with the inception of the first Brazilian national database of cardiovascular surgery in adults, the Brazilian Registry of Cardiovascular Surgeries in Adults (BYPASS) Registry [ 3 - 5 ] .…”
Section: Introductionmentioning
confidence: 99%